Where are we and where are we going in advanced non-small cell lung cancer with EGFR mutation? - Meza-Liviapoma, Jessica (2026)
Non–small cell lung cancer (NSCLC) remains one of the leading causes of cancer-related mortality worldwide. The identification of actionable mutations, particularly in the epidermal growth factor receptor (EGFR) gene, has substantially reshaped the therapeutic landscape of this disease. Tyrosine kinase inhibitors (TKIs) have consistently demonstrated improvements in progression-free survival and overall survival compared with conventional chemotherapy. However, acquired resistance inevitably develops in most patients, driven by secondary mutations, activation of alternative signaling pathways such as MET or HER2, or histologic transformation. In recent years, the management of EGFR-mutatedNSCLC has evolved toward more complex strategies, including first-line combination approaches, treatment intensification with chemotherapy, and the use of bispecific antibodies. In addition, targeted therapies have been developed for uncommon mutations, such as exon 20 insertions, and more recently, antibody-drug conjugates have expanded therapeutic options in the post-osimertinib setting. The objective of this review is to provide an updated overview of the current treatment landscape for advanced EGFR-mutated NSCLC and to discuss emerging strategies aimed at overcoming resistance mechanisms.